2018
DOI: 10.1177/0047287518790403
|View full text |Cite
|
Sign up to set email alerts
|

Thrilled to Have “Bagged a Bargain” or “Bitter” and “Very Frustrating”? Exploring Consumer Attitudes to Value and Deals in Tourism

Abstract: Similar to most global tourism markets, UK consumers adjusted their behavior during the global financial crisis, emphasizing value for money in travel choices. However, there is little evidence concerning consumers' value-seeking behavior and especially how deals, discounts and other sales promotions influence tourist decision making. This project explores concepts of value consciousness and deal proneness to shed light on attitudes towards monetary value in travel purchases. Using focus groups, the study foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…For example, when promoting TFTLC, a museum could display pictures and posters of celadon embryos and decorations to convey profound information about celadon craftsmanship and inheritors to visitors, thus promoting the product's connotations. With respect to advertising design and target market research, practitioners should consider different groups' emotional responses and cognition to create pleasing, exciting advertisements [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when promoting TFTLC, a museum could display pictures and posters of celadon embryos and decorations to convey profound information about celadon craftsmanship and inheritors to visitors, thus promoting the product's connotations. With respect to advertising design and target market research, practitioners should consider different groups' emotional responses and cognition to create pleasing, exciting advertisements [49].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers [48] have found that emotion has a positive influence on tourism attitude, whereas attitude has a partial mediating effect on emotion. Respondents may use a series of positive, negative, or mixed emotional words to express their attitudes towards value perceptions of tourism products during interviews [49]. Therefore, in this study, we combined emotion with attitude to create the notion of 'emotional attitude', which represents residents' attitudes towards ICH with respect to emotions.…”
Section: Effects Of Emotion On Behaviormentioning
confidence: 99%
“…The emotion results from a series of evaluations. Immediately following a purchase, customers question whether they made a wise decision (McCabe and Branco Illodo 2019). It is hard to assess tourism products prior to experiencing them; the subsequent uncertainty causes anxiety and discomfort.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Right after a booking has been completed, people question if they made a wise choice (McCabe and Branco Illodo 2019). Because of the nature of a hotel room being an experiential product, anxiety about a decision already made persists until the actual stay.…”
Section: Introductionmentioning
confidence: 99%
“…Los minoristas utilizan estrategias promocionales, como los productos destacados, los productos en oferta y los obsequios, para aumentar las ventas y las ganancias en mercados diversos (Andrade et al 2010;Chinchay-Villarreyes et al 2020;Choi & Chen, 2019;Guerreiro et al 2009;McCabe & Branco, 2019;Valencia et al 2019). Sin embargo, los descuentos en los precios y los paquetes de bonificación (bonus pack) son las estrategias de promoción de ventas más empleadas (Chen et al 2012).…”
Section: Bonus Pack Versus Precios De Descuentounclassified